The Implementation of Field Projects in Enhancing Understanding of People, Places, and Environmental Dynamics in Elementary Social Studies Learning (Lembaga Pengembangan Kinerja Dosen, 2025)
Social Studies (IPS) learning in elementary schools has tended to be theoretical and memorization-oriented, resulting in students being less able to connect the material with social and environmental realities. This study aims to examine the implementation of field projects as a contextual learning strategy in understanding the dynamics of humans, places, and the environment at the elementary school level. The research method used is a qualitative approach with literature studies, with data sources in the form of SINTA-indexed national journal articles, reputable international journals, and scientific books published in the last five to ten years. Analysis was carried out through literature selection, content analysis, and synthesis of findings. The results of the study indicate that field projects contribute to improving students' critical thinking skills, spatial understanding, social empathy, and ecological awareness. In addition, direct involvement in observation, interviews, and thematic project creation encourages students to see the relationship between humans, space, and the environment more holistically. The novelty of this study lies in the emphasis on the integration of field projects as an approach to elementary school social studies learning that unites social, geographical, and ecological aspects within the framework of the Independent Curriculum. These findings contribute to the development of project-based social studies learning models as well as practical recommendations for PGSD teachers in integrating field experiences into daily learning.